Dermoscopy of head melanoma-case studies and review of references - Irdina Drljevic; Kenan Drljevic (Our Dermatology Online, 2012)
Dermoscopy is valid, noninvasive technique for the visualization of different morphological structures within pigmented melanocytic skin lesion. In clinical practice, positive personal history is considered to be as an indication of increased melanoma risk. The thickness ofmelanoma (Breslow Index) is the most important independent predicting factor of survival for stage I patients.We aimed to present a two cases of head-melanoma and discuss prominent clinical and dermoscopic features across the spectrum of"hidden-melanoma" and differential diagnosis.